(untitled) (Research, Society and Development, 2020)
The idea that associated agro-industrial by-products only with the production of animal feed has been gradually being replaced, as the scientific community is interested in these products, as low-cost nutrients for the composition of food and/or culture media in research biotechnological to increase or improve nutrients or characteristics inherent in the raw material. Thus, this work aims to characterize input for baking with claim of natural fortification from the fermentation by Saccharomyces cerevisiae. For this, biomass was characterized in terms of its composition (ashes, fibers, lipids, proteins, and carbohydrates) and antioxidant activity of phenolic compounds. The results show an increase in nutrients such as ash, proteins and fibers, in addition the free and bound phenolic compounds present in the biomass showed antioxidant potential. Therefore, fermented rice bran is a potential input to be used in baking.